Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1002/jsfa.4204
|View full text |Cite
|
Sign up to set email alerts
|

Influence of heat on protein degradation, ultrastructure and eating quality indicators of pork

Abstract: Heating temperature has a great effect on eating quality indicators, protein degradation and ultrastructure of pork muscle fibres. .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
46
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 27 publications
9
46
0
1
Order By: Relevance
“…3). These results indicated that myofibrillar proteins exhibited higher thermal stability than the sarcoplasmic proteins, consistent with the findings of Huang et al (2011) Other myofibrillar protein bands also showed a deceasing trend (Fig. These results indicated that myofibrillar proteins exhibited higher thermal stability than the sarcoplasmic proteins, consistent with the findings of Huang et al (2011) Other myofibrillar protein bands also showed a deceasing trend (Fig.…”
Section: Sds-page Analysissupporting
confidence: 84%
See 1 more Smart Citation
“…3). These results indicated that myofibrillar proteins exhibited higher thermal stability than the sarcoplasmic proteins, consistent with the findings of Huang et al (2011) Other myofibrillar protein bands also showed a deceasing trend (Fig. These results indicated that myofibrillar proteins exhibited higher thermal stability than the sarcoplasmic proteins, consistent with the findings of Huang et al (2011) Other myofibrillar protein bands also showed a deceasing trend (Fig.…”
Section: Sds-page Analysissupporting
confidence: 84%
“…These reactions generally consist of aggregation, denaturation, and degradation of myofibrillar and sarcoplasmic proteins, and solubilization and gel formation of connective tissues (Kong et al 2008a;Isleroglu et al 2014;Kaur et al 2014). During cooking, the myofibrils structure changes progressively, including that the I bands become shortened and more condensed and that the A bands appear slightly stretched (Huang et al 2011;Dai et al 2014). During cooking, the myofibrils structure changes progressively, including that the I bands become shortened and more condensed and that the A bands appear slightly stretched (Huang et al 2011;Dai et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the moisture content of the control samples increased during marination and then decreased. Cooking reduced the moisture content of the samples (p<0.05) possibly due to the breakdown of proteins caused by heating (Huang 2010). Obuz & Cesur (2009) and Serdaroğlu et al (2007), evaluating chicken and turkey breast meat, respectively, indicated that the moisture content of the marinated samples was higher than that of marinated + cooked samples.…”
Section: Effect Of Marination With Fruit and Vegetable Juice On The Smentioning
confidence: 97%
“…Analogically to fresh meat, frozen meat reproduced the same myosin band pattern, decreasing after cooking at 140°C but remaining constant after heating at 60°C. Huang, Huang, Xu, and Zhou (2011) studying pork reported that myosin remained unchanged below 80°C and was then rapidly degraded, whereas actin showed no visible change at any temperature (25°C, 50°C, 60°C, 80°C and 100°C). It seems that actin is rather stable at temperature under 100°C as we observed.…”
Section: Aggregates Formationmentioning
confidence: 99%